2020
DOI: 10.1039/c9ra09790b
|View full text |Cite
|
Sign up to set email alerts
|

In vivo toxicity evaluation of two polyoxotungstates with potential antidiabetic activity using Wistar rats as a model system

Abstract: Study of the in vivo hypoglycemic effect, hepatotoxicity and nephrotoxicity of a donut-shaped polyanion salt (NH4)14[Na@P5W30O110]·31H2O {NaP5W30} and its Ag-containing derivative K14[Ag@P5W30O110]·22H2O·6KCl {AgP5W30}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…7 and 8). These ndings are consistent with our previously published studies regarding in vivo toxicity evaluation of POM-based compounds, suggesting that the kidney and liver are the vital positions of POM metabolism and elimination process [27,28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…7 and 8). These ndings are consistent with our previously published studies regarding in vivo toxicity evaluation of POM-based compounds, suggesting that the kidney and liver are the vital positions of POM metabolism and elimination process [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…These assumptions are in agreement with a previously published pharmacokinetics study reporting that the oral bioavailability of a POM-based promising drug, Cs 2 K 4 Na[SiW 9 Nb 3 O 40 ], in rats is low [26]. Moreover, in our previous toxicological studies on different polyoxotungstates, mild toxic effects were found after oral administration [27,28], which could be ascribed to the low oral bioavailability of POMs. Additionally, the low oral bioavailability indicates that WD-POM and its related compounds could be a good platform for the development of a new generation of POM-based oral CT contrast agents and suggests the need for further study of absorption and elimination after oral administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the design of cheap, safe and efficient enzyme inhibitors has become the focus of research.POMs has many biological activities due to their unique structural and functional properties, including the inhibition of α-glucosidase. Dinčić et al 18 used Wistar rats as a model system to evaluate the in vivo toxicity of two polyoxotungstates ((NH 4 ) 14 [ anti-diabetic activity. The results show that both substances have hypoglycemic effects in rats, but there is certain toxicity (mild liver toxicity, nephrotoxicity).…”
Section: α-Glucosidasementioning
confidence: 99%
“…Besides, some studies have shown that tungstate can stimulate the functional regeneration of islet B cells in animals, can prevent ALR1 and ALR2-mediated polyol pathway and related AGEs, can effectively reduce blood glucose levels in vivo and in vitro, and prevent related complications. 21 Dinčić et al 18 studied the hepatotoxicity and nephrotoxicity induced by POMs in mice for two weeks, and the results showed that the effect was mild.…”
Section: α-Glucosidasementioning
confidence: 99%